Akuntabilitas Pelayanan Publik Pada Layanan Parkir Tepi Jalan di Wilayah Kota Denpasar - Luh Tu Anggarayani; Komang Ema Marsitadewi; I Putu Adi Permana Putra (Public Administration Dept, Faculty of Social and Political Science, 2026)
The background of this research based on the problems in roadside parking services in Denpasar City. As a public service that is closely related to people's daily lives, problems related to roadside parking services often become the focus of public attention. Public complaints through the Pro Denpasar media on April 2, 2024 and the finding that parking facilities for roadside parking services not fulfilled as regulated in Peraturan Wali Kota Denpasar No. 64 Tahun 2023 tentang Penyelengaraan Perparkiran Pasal 12 ayat (1) point b as well as the amount of levies received from roadside parking services in Denpasar City are the basis for knowing how the accountability of public services is. The method used in this research is descriptive qualitative with data collection techniques of observation, interviews, and documentation. This research involved 4 informants consisting of Dinas Perhubungan Kota Denpasar, Perumda Bhukti Praja Sewakadarma, Juru Parkir (parking attendantthe) and people who use parking services. Determination of informants in this research uses the technique purposive sampling and incidental sampling. Data analysis techniques use analysis techniques according to Miles and Huberman. The indicators used are the four dimensions of public service accountability according to Elwood (1993) which consist of accountability for probility and legal accountability, process accountability, program accountability, and policy accountability. The results of this study indicate that of the four dimensions of public service accountability, three dimensions of accountability, namely accountability for probility and legal accountability, process accountability, and program accountability have been fulfilled in the implementation of roadside parking services in Denpasar City. There is one dimension, namely the accountability of the policy for implementing roadside parking services in Denpasar City, which has not been fulfilled.